SUMBANGSIH PEMIKIRAN KYAI HAJI AGUS SALIM DALAM PENDIDIKAN ISLAM - Dwi Trisna Wati (STAI Sebelas April Sumedang, 2023)
Education has contributed to advancing a nation, even human civilization itself, education has an important value in human daily life. Education in life is not only about formality education but in religious applications, as well as education that is oriented towards Islamic values. Islamic education according to Hamka is an effort to guide and provide knowledge based on Islamic teachings to children, so that one day they can understand and practice Islamic teachings. Through education, human beings will grow and develop rapidly to keep up with the times and the demands of people's lives. Islam is an advanced religion, but the view of Islam in Indonesian society has a different meaning due to misinformation provided by the Dutch government (Mukayat, 1985: 10), thus causing a gap between the modern world and Islam at that time. Therefore, it is necessary to have real Islamic religious education, namely as a religion of progress. Muslim youths must submit their knowledge and live religiously, a sense of nationality should also be imbued with religious ideals. Education according to Haji Agus Salim is something that is contained in the pillars of Islam and on the commands and prohibitions of Islam. Haji Agus Salim is a Muslim intellectual figure who is liked by many figures and is able to pass on his thoughts on the teachings of Islam as well as politics to generations of secular but faithful western-educated Muslims.